A fine‐scale genetic linkage map reveals genomic regions associated with economic traits in walnut (Juglans regia). (27th May 2019) - Aradhya, Mallikarjuna K.; Velasco, Dianne; Wang, Ji‐Rui; Ramasamy, Ramesh; You, Frank M.; Leslie, Chuck; Dandekar, Abhaya; Luo, Ming‐Cheng; Dvorak, Jan
Abstract: A genetic linkage map of walnut containing 2, 220 single nucleotide polymorphisms (SNPs) in 16 linkage groups (LGs) was constructed using an F1 mapping population from a cross between "Chandler" and "Idaho, " two contrasting heterozygous parents. Five quantitative yield traits, lateral fruitfulness, harvest date and three nut traits (shell thickness, nut weight and kernel fill) were then mapped on to linkage groups. A significant quantitative trait locus (QTL) in LG 11 with negative additive effects suggested heterozygote superiority in the expression of lateral bearing. A set of three QTLs explaining 10% of the variation in harvest date was located in LG 1. Shell thickness, nut weight and kernel fill were under the control of two to three linked pleiotropic QTLs in LG 1 segregating from "Idaho." The marginal positive additive effects of QTLs for harvest date, shell thickness and nut weight and small negative additive effects for kernel fill suggested that the QTLs had a marginal effect on the expression of these traits.